Describing function analysis of mechanical systems with nonlinear friction and backlash phenomena - Barbosa, Ramiro (2019)
This paper analyses the dynamical properties of systems with nonlinear friction and backlash phenomena based on the describing function method. The dynamics is illustrated using the Nyquist and Bode plots and the results are compared with those of standards models.